Financial Analysis of Jatropha Plantations in the context of Nepal - Adhikari, Narayan Prasad; Wegstein, Michael (Journal of the Institute of Engineering, 2011)
In general two scenarios for Jatropha plantations are considered to be realistic for Nepal. The first scenario concentrates on the Terai region. In this area large-scale plantations seem to be possible for example in locations formerly subjected to flooding. The plantations can be set up within a professional context – meaning to provide the necessary inputs (fertilizer, labour) for maximising yields. Using this sort of wasteland Jatropha can be used to produce straight vegetable oil (SVO) for the direct use in water pumps or modified engines or – if the yield exceeds the demand for SVO, with establishing transesterification-units the SVO can be transformed into biodiesel. With water pumps crops can be increased from one yield per year up to three yields per year with irrigation. The second scenario concentrates on the hill region. In this context Jatropha is considered as being part of poverty alleviation strategies. Per household 500 plants could be planted as a fence, along roads, against erosion or around the leasehold forestry areas. In this scenario no plant care besides some cutting and weeding is assumed. Accordingly the yield is expected to be lower than in the first scenario. For hill areas the SVO will mainly find application for lightning or running processing mills, pumps, generators or tractors. Replacing Kerosene and Diesel in modified engines and lamps will be the best application for the hill areas. Transforming SVO into biodiesel is economically not viable and efficient as the analysis will show. Key Words: Biofuel; Jatropha; Financial analysis; Renewable energies; Transesterification; Jatropha plantation; Biodiesel; Cash flow analysis DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5105 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 143-148 Uploaded Date: 20 July, 2011